Providing dental insurance can positively impact oral health outcomes in Ontario - Nevena Zivkovic; Musfer Aldossri; Noha Gomaa; Julie W. Farmer; Sonica Singhal; Carlos Quiñonez; Vahid Ravaghi (BMC, 2020)
Abstract Background Universal coverage for dental care is a topical policy debate across Canada, but the impact of dental insurance on improving oral health-related outcomes remains empirically unexplored in this population. Methods We used data on individuals 12 years of age and older from the Canadian Community Health Survey 2013-2014 to estimate the marginal effects (ME) of having dental insurance in Ontario, Canada's most populated province (n = 42,553 representing 11,682,112 Ontarians). ME were derived from multi-variable logistic regression models for dental visiting behaviour and oral health status outcomes. We also investigated the ME of insurance across income, education and age subgroups. Results Having dental insurance increased the proportion of participants who visited the dentist in the past year (56.6 to 79.4%, ME: 22.8, 95% confidence interval (CI): 20.9-24.7) and who reported very good or excellent oral health (48.3 to 57.9%, ME: 9.6, 95%CI: 7.6-11.5). Compared to the highest income group, having dental insurance had a greater ME for the lowest income groups for dental visiting behaviour: dental visit in the past 12 months (ME highest: 17.9; 95% CI: 15.9-19.8 vs. ME lowest: 27.2; 95% CI: 25.0-29.3) and visiting a dentist only for emergencies (ME highest: -11.5; 95% CI: − 13.2 to − 9.9 vs. ME lowest: -27.2; 95% CI: − 29.5 to − 24.8). Conclusions Findings suggest that dental insurance is associated with improved dental visiting behaviours and oral health status outcomes. Policymakers could consider universal dental coverage as a means to support financially vulnerable populations and to reduce oral health disparities between the rich and the poor.